1977
DOI: 10.1136/gut.18.7.543
|View full text |Cite
|
Sign up to set email alerts
|

Cholelithiasis in subjects with hypercalcaemia and primary hyperparathyroidism detected in a health screening.

Abstract: SUMMARY The frequency of gallstone disease was studied in a group of 82 subjects (69 females and 13 males; mean ages 55*0 and 52-3 years, respectively) with verified hypercalcaemia (VHC) detected in a health screening in the Stockholm area. All non-cholecystectomised subjects were examined with a peroral cholecystography. Causes of hypercalcaemia other than primary hyperparathyroidism (PHPT) had been excluded as far as possible. Sixty-two patients had been operated upon and all but two males were found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
4

Year Published

1984
1984
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
0
7
1
4
Order By: Relevance
“…However there are papers which are at variance with those of other investigators who have reported that primary hyperparthyroidism is associated with an abnormally high frequency of gallstone disease (8).…”
Section: Introductioncontrasting
confidence: 52%
“…However there are papers which are at variance with those of other investigators who have reported that primary hyperparthyroidism is associated with an abnormally high frequency of gallstone disease (8).…”
Section: Introductioncontrasting
confidence: 52%
“…Increased body weight has also been associated with gallstone disease (46) and an increased risk of death from a variety of cancers, including those of the gastrointestinal tract, kidney, breast, and female reproductive tract (67). Cholelithiasis (68,69) and increased cancer occurrence (13,14) and mortality from cancer (12) have also been reported in association with primary hyperparathyroidism. Thus, increased body weight may contribute to the reported associations between primary hyperparathyroidism and these seemingly unrelated conditions.…”
Section: Discussionmentioning
confidence: 96%
“…One of every 500 women and one of every 2,000 men older than 40 years have primary hyperparathyroidism [5][6][7][8][9]. The disease is particularly prevalent in postmenopausal women.…”
Section: The Shifting Paradigm: a Historical Prospectivementioning
confidence: 98%